Adverse drug reaction profile of anticancer agents in a tertiary care centre of rural Maharashtra: a cross-sectional study - Agrawal, Palak; Narwane , Sandeep; Gulve , Priyanka; Kolhe , Prajakta; Singhal , Shreya; Goyal , Sonakshi; Shukla , Amitesh (International Journal of Research in Medical Sciences, 2023)
Background: The present study was undertaken to analyse the clinical spectrum, pattern of ADR reported, most common suspected drugs, timing of reporting of suspected ADR, outcome, severity and causality assessment of adverse drug reactions among oncology patients reported at our ADR monitoring Centre. Methods: The descriptive cross-sectional study was carried out for two months in the oncology department of a tertiary care rural hospital. ADR reporting form Version 2.4 was used for recording information of all patients of any gender and age who were suspected cases of adverse drug reactions receiving chemotherapy. Results: Total 83 ADRs were reported within the duration of two months. The number of males and females were 21 and 62, respectively with mean age 56.9±11.6 years for males and 59.6±8.8 years for females. The age group most commonly reported with suspected ADR was 61-70 years (28.9%). Of the 83 ADR reported, the most common suspected drug was Paclitaxel (47, 56.6%). The most common indications for the use of these anticancer drugs was reported to be CA breast (43, 51.8%). Most of the ADRs (38, 45.8%) were reported immediately. On applying Naranjo’s Causality Assessment Scale, 61 and 22 ADRs fell in the category of Probable and Possible, respectively. Conclusions: The occurrence of ADR among patients on chemotherapy is high. The reported ADR were common and predictable. Hence diligent monitoring in ADR may help manage and prevent morbidity associated with anti-cancer drugs.